2018
DOI: 10.14704/nq.2018.16.6.1662
|View full text |Cite
|
Sign up to set email alerts
|

Career Planning Decision-making of College Students Based on Cognitive Science

Abstract: Under severe employment pressure and competition conditions, it is the first issue for college students to make career planning decisions suitable for their own development, which is of great significance for improving college students' career efficacy and career maturity. This paper studies the career planning decision-making of college students based on cognitive science theory. The results show that career decision-making should emphasize the relationship between human and information, and human and value, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…This behavior and misconception actually wastes learning and training opportunities that can improve their professional qualities. [10]. The second is poor professional psychological quality.…”
Section: Inaccurate Career Positioning and Poor Professional Psycholo...mentioning
confidence: 99%
“…This behavior and misconception actually wastes learning and training opportunities that can improve their professional qualities. [10]. The second is poor professional psychological quality.…”
Section: Inaccurate Career Positioning and Poor Professional Psycholo...mentioning
confidence: 99%
“…It is one competence of career development control [ 43 ], and it is closely related to the core concept of career maturity. It is demonstrated that a high career maturity equates to a strong planning ability [ 44 ]. Scholars from different countries have studied career planning abilities in different student groups, such as nursing students [ 45 , 46 ], vocational high school students [ 47 ], community college students [ 48 , 49 ], first-year students, and university students [ 1 , 50 , 51 ].…”
Section: Theories and Hypotheses Developmentmentioning
confidence: 99%
“…Career-planning ability is an essential concept related to career maturity. Studies have supported that high career maturity is a strong planning ability [54,55]. As career maturity is one fundamental resource of CDMSE, it is rational to investigate the relationship between career-planning ability with CDMSE.…”
Section: Career-planning Abilitymentioning
confidence: 99%